Long-term complications and outcomes of therapeutic embolization of cerebral arteriovenous malformations: a systematic review - Lúcio, Vivianne Beatriz dos Santos; Queiroz, Vinício Rufino; Lins, Cícero José Pacheco; Baggio, Jussara Almeida de Oliveira; Souza, Carlos Dornels Freire de (São Paulo Medical Journal, 2025)
BACKGROUND: Embolization is a promising treatment strategy for cerebral arteriovenous malformations (AVMs). However, consensus regarding the main complications or long-term outcomes of embolization in AVMs remains lacking. OBJECTIVE: To characterize the most prevalent complications and long-term outcomes in patients with AVM undergoing therapeutic embolization. DESIGN AND SETTING: This systematic review was conducted at the Federal University of Alagoas, Arapiraca, Brazil. METHODS: This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses criteria. Data were obtained from MEDLINE, PubMed, LILACS, and SciELO databases, which included the epidemiological profile of the population, characteristics of the proposed therapy, complications (hemorrhagic events and neurological deficits), and long-term outcomes (modified Rankin scale pre- and post-treatment, AVM recanalization, complete obliteration, and deaths). RESULTS: Overall, the analysis included 34 articles (2,799 patients). Grade III Spetzler–Martin AVMs were observed in 34.2% of cases. Notably, 39.3% of patients underwent embolization combined with radiosurgery. The most frequently reported long-term complication was hemorrhage, which occurred in 8.7% of patients at a mean follow-up period of 58.6 months. Further, 6.3% of patients exhibited neurological deficits after an average of 34.7 months. Complete obliteration was achieved in 51.4% of the cases after a mean period of 36 months. Recanalization of AVMs was observed in 3.5% of patients. Long-term death occurred in 4.0% of patients. CONCLUSION: Embolization of AVMs is an increasingly safe strategy with low long-term complications and satisfactory outcomes, especially in patients who have undergone combination therapies. SYSTEMATIC REVIEW REGISTRATION: https://www.crd.york.ac.uk/prospero/ Registration number CRD42020204867